2021
DOI: 10.1038/s41746-021-00410-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of mobile applications in chronic disease management: a scoping review

Abstract: While there has been a rapid growth of digital health apps to support chronic diseases, clear standards on how to best evaluate the quality of these evolving tools are absent. This scoping review aims to synthesize the emerging field of mobile health app quality assessment by reviewing criteria used by previous studies to assess the quality of mobile apps for chronic disease management. A literature review was conducted in September 2017 for published studies that use a set of quality criteria to directly eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 53 publications
1
50
0
Order By: Relevance
“…Nonetheless, none of these was implemented in the peer-reviewed studies identified, emphasising the preference for parallel-group RCTs or checklists of quality criteria that show significant variability and no clear method for their development 132 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, none of these was implemented in the peer-reviewed studies identified, emphasising the preference for parallel-group RCTs or checklists of quality criteria that show significant variability and no clear method for their development 132 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding methods for evaluating mHealth tools, a recent scoping review summarizing quality assessment methods for mobile apps in chronic disease management found minimal agreement on the most appropriate criteria for evaluating mobile apps, with only 18% (12/65) of apps including evidence-based health information, 22% (14/65) using a behavioral change framework, and 37% (24/65) applying usability metrics as quality criteria for app assessment [ 51 ]. On the basis of the gaps identified in the analysis and practice methods for evaluating mobile apps, the authors proposed 3 primary goals for building quality criteria for app assessment: (1) prioritize existing evidence and knowledge against ease of assessment (eg, using patient-reported outcomes vs app ratings), (2) emphasize principles of behavior change theory, and (3) explicitly incorporate the patient perspective.…”
Section: Discussionmentioning
confidence: 99%
“…However, the constant creation and turnover of new apps can make this task difficult and time-consuming. Although syntheses of eHealth resources are becoming more common, their methodological and reporting quality require improvement so as to be more accessible to nonexperts [ 16 ]. Further, there continues to be significant variation in quality criteria employed for assessment, with no clear method for developing the included criteria.…”
Section: Introductionmentioning
confidence: 99%